Cost effectiveness of TAPP (trans-abdominal pre-peritoneal inguinal hernia repair) over open inguinal Lichtenstein meshplasty - Kashyap, Manish Kashyap; Singhade, Pravin; Bora, Riddhi; Batra, Gaurav; Rege, Ishant; Chakrabarti, Roshni; Bora, Siddhi (International Surgery Journal, 2018)
Background: Hernia surgery has undergone tremendous refinement in technique of various methods have been advocated by different authors but each has got its own merit. Laparoscopic Trans-abdominal Pre-Peritoneal inguinal meshplasty (TAPP) is a newer technique which results in less post-operative pain, better cosmetic result, improves recovery time. The aim of the study was to compare cost effectiveness and duration of hospital stay that occurs from both laparoscopic TAPP repair and Lichtenstein repair in patients of inguinal hernia. Methods: The present study comprises 25 cases underwent open Lichtenstein mesh repair and 25 cases underwent laparoscopic (TAPP) repair. After surgery all patients were monitored carefully for pain, infection, cost effectiveness and hospital stay. Results: In present study, Group A is having significantly more cost of treatment than Group B in unilateral. The hospital stay was significantly low in group A than Group B. Conclusions: TAPP repair is more expensive compared to Lichtenstein’s meshplasty, TAPP repair is associated with faster recovery as compared to open Lichtenstein meshplasty, hospital stay is lesser in TAPP as compared to open inguinal meshplasty.